ANALISIS PENGARUH EKSPOR MIGAS, EKSPOR NON MIGAS DAN PENANAMAN MODAL ASING TERHADAP PERTUMBUHAN EKONOMI INDONESIA TAHUN 2000-2019 - martin Luter purba; Meiline Sihombing; Jusmer Sihotang (Fakultas Ekonomi dan Bisnis, Universitas HKBP Nommensen, 2021)
This study determines the effect of oil and gas exports, non-oil exports, foreign investment in Indonesia’s economic growth in 2000-2019. The data used is secondary data got from the Central Statistics Agency of Indonesia and Bank Indonesia. Data collection starts from 2000 to 2019. I process the data using the SPSS 16.0 program. The results of the analysis show that oil and gas exports have a positive and significant impact on Indonesia’s economic growth in 2000-2019, non-oil exports have a positive and significant impact on Indonesia’s economic growth. In 2000-2019, foreign investment had a negative and insignificant effect on Indonesia’s economic growth in 2000-2019. Based on the F test, together, oil and gas exports, non-oil exports, and foreign investment have a significant effect on Indonesia’s economic growth in 2000-2019.